Automatização robótica de processos financeiros - automatização de processos financeiros SAP pela introdução de RPA - Lopes, Carlos Alberto Ribeiro (2021)
Project Work presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence